Prevalence and Factors Associated with Sarcopenia in Chronic Kidney Disease Patients Undergoing Dialysis: A Single Center, Cross-sectional Study - Fauliza Rakhima; Ria Bandiara; Rudi Supriyadi; Lazuardhi Dwipa (Indonesian Journal of Kidney and Hypertension, 2025)
Background: Sarcopenia is associated with worse outcomes in stage 5 Chronic Kidney Disease on dialysis (CKD 5D) patients, influenced by various diagnostic criteria and patient characteristics. Nonetheless, the factors contributing to sarcopenia in CKD 5D remain underexplored. Objective: To investigate the prevalence and factors associated with sarcopenia in the CKD 5D population. Methods: An observational cross-sectional study was conducted on 132 CKD 5D patients (≥18 years old, dialysis ≥ 3 months) at Hasan Sadikin Hospital from July to August 2024. Descriptive statistics, bivariate analysis, and logistic regression were utilized to determine the prevalence of sarcopenia and its association with the Simplify Creatinine Index (SCI), physical activity, nutritional status, phosphate, and calcium serum levels. Hand Grip Strength (HGS) assessed muscle strength, Bioelectrical Impedance Spectroscopy (BIS) measured muscle mass, the 6-meter walk test evaluated physical performance, and the Asian Working Group for Sarcopenia (AWGS) 2019 criteria were employed for diagnosing sarcopenia. Results: Sarcopenia prevalence was 15.9%. Bivariate analysis revealed significant correlations with underweight (p=0.014), malnutrition (p=0.041), phosphate serum level (p=0.047), and calcium serum level (p=0.043). Logistic regression indicated that higher serum levels of calcium and phosphate and healthy nutritional status, served as protective factors against sarcopenia, with odds ratios of 0.677 (OR 0.677; CI 95% 0.493-0.93 and OR 0.313; CI 95% 0.130-0.755). Conclusion: Sarcopenia prevalence was 15.9%. Phosphate and calcium serum levels, underweight, and malnutrition were significantly correlated with sarcopenia. Higher serum phosphate and calcium levels, higher body weight, and good nutrition status were protective factors against sarcopenia in CKD 5D patients.